2018
DOI: 10.1073/pnas.1803361115
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of alternative splicing evolution during sunflower domestication

Abstract: Alternative splicing enables organisms to produce the diversity of proteins necessary for multicellular life by using relatively few protein-coding genes. Although differences in splicing have been identified among divergent taxa, the shorter-term evolution of splicing is understudied. The origins of novel splice forms, and the contributions of alternative splicing to major evolutionary transitions, are largely unknown. This study used transcriptomes of wild and domesticated sunflowers to examine splice differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 41 publications
2
52
0
Order By: Relevance
“…While introns do add noncoding length to genes, thus incurring costs during cell division and transcription, they offer the potential benefit of alternative splicing, contributing valuable flexibility in gene expression and regulation (Dibb, 1993;Jo & Choi, 2015;Lynch et al, 2006;Smith et al, 2018). Alternative splicing may in fact confer greater genetic flexibility to the mitochondrial genomes of plants and fungi compared to those of the relatively intron-poor bilateral animals (Dibb, 1993;Jo & Choi, 2015;Kazan, 2003;Keren, Lev-Maor, & Ast, 2010;Lynch et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…While introns do add noncoding length to genes, thus incurring costs during cell division and transcription, they offer the potential benefit of alternative splicing, contributing valuable flexibility in gene expression and regulation (Dibb, 1993;Jo & Choi, 2015;Lynch et al, 2006;Smith et al, 2018). Alternative splicing may in fact confer greater genetic flexibility to the mitochondrial genomes of plants and fungi compared to those of the relatively intron-poor bilateral animals (Dibb, 1993;Jo & Choi, 2015;Kazan, 2003;Keren, Lev-Maor, & Ast, 2010;Lynch et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on gene expression focus on expression abundance (the number of transcripts for a whole gene). However, alternative splicing resulting in the difference of transcript proportions can also contribute to adaptation (Barbosa-Morais et al 2012; Gamazon and Stranger 2014; Smith et al 2018). Therefore, understanding the transcriptomic basis of parallel phenotypic evolution requires studies of both expression abundance and alternative splicing, although the latter aspect has rarely been studied.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, other authors [ 43 ] analyzing transcriptomes of wild and domesticated sunflowers have identified differential splicing divergence related to domestication, especially through intron retention. Differential splicing has been related to genes involved in functions related to seed development.…”
Section: Introductionmentioning
confidence: 99%